Religion and Biopolitics in the Time of Corona: The Catholic Feast of Corpus Christi in a Polish City - Maćkowiak, Anna M. (Journal for the study of religion, nature and culture, 2022)
We explored the Corona pandemic through the nexus of the biopolitics of the Catholic Church and the state in Poland. We reflected on how religion in the pandemic crisis manages social lives, citizenship, and social control, superseding state biopolitics. The observation of the 2020’s Corpus Christi festival in Kraków and the analysis of sermons delivered by Polish Catholic leaders are at the core of our argument. They were followed by LGBTQ+ and women’s protests. While the Polish state has strived for totalizing control of individual bodies and people’s behavioral reactions in response to the threat of coronavirus, the Catholic Church’s biopolitics have focused on moral community, the exclusion of LGBTQ+ people and women’s rights activists, and redefining the Polish public sphere.